2013
DOI: 10.1590/1678-7757201302254
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric analysis of crown discoloration induced by MTA- and ZnOE-based sealers

Abstract: Crown discoloration can be induced by root canal sealer remnants following root canal treatment.Objective:The aim of this study was to evaluate chromatic alterations in human tooth crowns induced by a Mineral Trioxide Aggregate-based sealer (MTA Fillapex® and a commonly used ZnOE-based sealer (Roth-811). The tested null hypothesis was that the application of the materials did not induce clinically perceptible crown discoloration (Ho: CIE color difference ΔE<3.7).Material and Methods:Forty five fully developed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 29 publications
2
39
2
6
Order By: Relevance
“…According to many researchers, bismuth is associated with the discoloration of bioceramic materials and tooth tissue [3739]. However, Ioannidis et al compared in vitro MTA Fillapex with Roth-811 cement and found that the application of MTA-based root canal sealer results in minimal color alterations of tooth tissues (not clinically perceptible discoloration), whereas zinc oxide-eugenol cement induces severe discoloration [40]. …”
Section: Discussionmentioning
confidence: 99%
“…According to many researchers, bismuth is associated with the discoloration of bioceramic materials and tooth tissue [3739]. However, Ioannidis et al compared in vitro MTA Fillapex with Roth-811 cement and found that the application of MTA-based root canal sealer results in minimal color alterations of tooth tissues (not clinically perceptible discoloration), whereas zinc oxide-eugenol cement induces severe discoloration [40]. …”
Section: Discussionmentioning
confidence: 99%
“…It features the advantages of simplicity, reproducibility, and objectivity. Illuminant D65 was chosen because it corresponds to the tooth color appearance in daylight . The average Δ E value that can be judged as a match with visual criteria in the oral cavity environment was 3.7 .…”
Section: Discussionmentioning
confidence: 99%
“…The CIE system has been recognized by the ISO 28 and extensively used in dental research. 21,25,28,29 It features the advantages of simplicity, reproducibility, and objectivity. Illuminant D65 was chosen because it corresponds to the tooth color appearance in daylight.…”
Section: Discussionmentioning
confidence: 99%
“…This sealer is composed of salicylate resin, resin diluent, natural resin, bismuth oxide, silica nanoparticles, and MTA. Its physical properties (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and biocompatibility (24,25) are already known. Nonetheless, to date, no studies have been conducted to analyze histologically the effect of MTA Fillapex in direct contact with bone tissue.…”
mentioning
confidence: 99%